Effectiveness and safety of tripterygium wilfordii poly-glycosides on glomerulonephritis: a systematic review and meta-analysis - Yan, Xiaolin; Shi, Juan; Zhang, Yingying; Liu, Juan; Lin, Xiaoqing; Yu, Chungang; Li, Xiao (Frontiers in Pharmacology, 2024)
Treatment of glomerulonephritis presents several challenges, including limited therapeutic options, high costs, and potential adverse reactions. As a recognized Chinese patent medicine, Tripterygium wilfordii poly-glycosides (TWP) have shown promising benefits in managing autoimmune diseases. To evaluate clinical effectiveness and safety of TWP in treating glomerulonephritis, we systematically searched PubMed, Cochrane Library, Web of Science, and Embase databases for controlled studies published up to July 12, 2023. We employed weighted mean difference and relative risk to analyze continuous and dichotomous outcomes. This meta-analysis included 16 studies that included primary membranous nephropathy (PMN), type 2 diabetic kidney disease (DKD), and Henoch-Schönlein purpura nephritis (HSPN). Analysis revealed that additional TWP administration improved patients' outcomes and total remission rates, reduced 24-hour urine protein (24hUP) and decreased relapse events. The pooled results demonstrated the non-inferiority of TWP to glucocorticoids in achieving total remission, reducing 24hUP, and converting the phospholipase A2 receptor (PLA2R) status to negative. For DKD patients, TWP effectively reduced 24hUP levels, although it did not significantly improve the estimated glomerular filtration rate (eGFR). Compared to valsartan, TWP showed comparable improvements in 24hUP and eGFR levels. In severe cases of HSPN in children, significant clinical remission and a reduction in 24hUP levels were observed with the addition of TWP treatment. TWP did not significantly increase the incidence of adverse reactions. Therefore, TWP could offer therapeutic benefits to patients with PMN, DKD, and severe HSPN, with a minimal increase in the risk of side effects.